Cross-language distance influences receptive vocabulary outcomes of bilingual children. Issue 2 (April 2020) - Blom, Elma; Boerma, Tessel; Bosma, Evelyn; Cornips, Leonie; van den Heuij, Kirsten; Timmermeister, Mona
Various studies have shown that bilingual children score lower than their monolingual peers on standardized receptive vocabulary tests. This study investigates if this effect is moderated by language distance. Dutch receptive vocabulary was tested with the Peabody Picture Vocabulary Test (PPVT). The impact of cross-language distance was examined by comparing bilingual groups with a small (Close; n = 165) and a large between-language distance (Distant; n = 108) with monolingual controls ( n = 39). As a group, the bilinguals scored lower on Dutch receptive vocabulary than the monolinguals. The bilingual Distant group had lower receptive vocabulary outcomes than the bilingual Close and monolingual groups. No difference emerged between the monolinguals and the bilingual Close group. It can be concluded that bilingual children whose languages provide ample opportunities for transfer and sharing knowledge do not have any receptive vocabulary delays. The findings underscore that bilingual children cannot be treated as a homogeneous group and are important for determining which bilingual children are at risk of low vocabulary outcomes.